OC-062 A comparative study of laparoscopic vs open cystgastrostomy for pancreatic pseudocysts. (28th May 2012) - Malde, D J; Khaled, Y; Fox, T; Laftsidis, P; De Liguori, N; Deshpande, R; O'Reilly, D; Sherlock, D; Ammori, B J
Abstract : Introduction: While large and persistent pancreatic pseudocysts are amenable to internal drainage by laparoscopic techniques, the benefits of this minimally invasive approach remain to be demonstrated. The aim of this study was to compare the open and laparoscopic approaches for internal drainage of large and persistent pancreatic pseudocysts. Methods: Patients who underwent cystgastrostomy were selected, and the demographic features, clinical characteristics and outcomes of those who had the surgery performed laparoscopically were compared to those who had open surgery. The two approaches were compared on an intention-to-treat basis. Data shown represent medians. Results: Between 1997 and 2010, 42 patients (15 female and 27 male) underwent 45 surgical internal drainage procedures for pancreatic pseudocysts (36 laparoscopic with two conversions to open surgery, and nine open). The laparoscopic and open groups were comparable for age (56 vs 53 years, p = 0.448), sex distribution, and size of pseudocyst (12 vs 13 cm, p = 0.305). The two approaches had comparable operating times (90 vs 75 min, p=0.630) but laparoscopic surgery carried a significantly lower risk of postoperative morbidity (5.8% vs 54.5%, p=0.001) and shorter postoperative hospital stay (2 vs 10.5 days, p<0.001). Laparoscopic surgery was also associated with a more rapid resumption of dietary intake (median 4 vs 6 days, p = 0.065). There was one death in the open group (11.1%) but none in the laparoscopic group. Conclusion: The laparoscopic approach to cystgastrostomy for large and persistent retrogastric pancreatic pseudocysts is associated with a smoother and more rapid recovery and a shorter hospital stay compared with open surgery. Competing interests: None declared.